The diagnostic difficulties of eosinophilia in clinical practice - case series - Szymczyk, Agnieszka; Szydełko, Magdalena; Szydełko, Joanna; Jaworski, Jakub; Onyshchuk, Yuliya; Dziedzic, Rafał; Hus, Marek; Podhorecka, Monika (Journal of Education, Health and Sport, 2019)
Introduction: Eosinophilia, defined as elevated level of eosinophils in peripheral blood above 5 x 109/L, is the hematological disorder, which may occur in multiple conditions, such as allergies, gastrointestinal, autoimmune diseases, parasite, fungal infections as well as drug related eosinophilia. Although hematological causes of eosinophilia (idiopathic, myeloproliferative and lymphocytic variant) should be taken into consideration.Aim of the study: The aim of our study was to performed the difficulties related to the differential diagnosis of eosinophilia, especially associated with the diverse symptoms. Materials and methods: The study included 5 patients hospitalized in the Department of Hematooncology and Bone Marrow Transplantation, due to eosinophilia associated with diverse symptoms. Medical history, physical examination, the peripheral blood as well as bone marrow samples analysis and the genetic tests for the presence of mutations or rearrangements that detect leukemia or lymphoma were analyzed. Moreover, patients were evaluated due to the presence of parasites. Results: The case series revealed that eosinophilia may have a various etiological background. Three patient demonstrated the reactive eosinophilia, caused by bacterial, parasite infections and eosinophilic granulomatosis with polyangitis, however in two other cases the chronic eosinophilic leukemia with abnormalities of PDGFRA were diagnosed. Conclusions: Eosinophilia is an important diagnostic and prognostic feature in a varied range of pathological conditions from infections, allergies to malignancies. For this reason, it is an enormous diagnostic as well as therapeutic challenge and requires an interdisciplinary clinical approach, especially in cases with unclear manifestations.